Use of Povidone-Iodine Drop Instead of Sub-Conjunctival Injection of Dexamethasone and Gentamicin Combination at the end of Phacoemulsification Cataract Surgery - Ahmed, MS; Moly, KN; Aziz, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):232-5. The abstract of this article is available on the PubMed website